Interface formation and deformation behaviors of an additively manufactured nickel-aluminum-bronze/15-5 PH multimaterial via laser-powder directed energy deposition - Li, Boyuan (2022)
Additive manufacturing (AM) of a nickel-aluminum-bronze (NAB)/15-5 PH multimaterial by laser-powder directed energy deposition (LP-DED) accomplished a combination of excellent mechanical performance and high corrosion resistance. An NAB/15-5 PH interface without cracks and lack of fusion was achieved, which was characterized with an interlayer of FexAl dendrites. The formation of the interfacial characteristics was attributed to a synthetic effect of liquid phase separation, Marangoni convection, and atom diffusion. A miscibility gap was generated by a high degree of supercooling in the melt pool, and 15-5 PH solidified prior to NAB to form a dendritic interlayer. Marangoni convection occurred to promote the Al atom diffusion from NAB to 15-5 PH, contributing to the formation of the FexAl phase at the interface. The multimaterial sample possessed higher ultimate tensile strength of 754.64 MPa in the transverse direction and 854.57 MPa in the longitudinal direction as compared to that of copper/steel counterparts fabricated by AM. The multimaterial printed by LP-DED exhibited different deformation mechanisms in the transverse and longitudinal directions. In the transverse direction, NAB contributed more deformation than 15-5 PH and determined the improved ductility of the multimaterial; in the longitudinal direction, the brittle FexAl dendrites constrained the deformation of NAB and 15-5 PH, which resulted in the early failure of the multimaterial. The multimaterial tended to undergo cracking at the interface of the FexAl and Cu phases under stress concentration, which was induced by their crystal incoherence.